Evidence on Euromediterranean Trade Integration: The Case of German Olive Oil Imports - Aikaterini Kavallari; Sarah Maas; P. Michael Schmitz (German Journal of Agricultural Economics (GJAE), 2010)
The deepening of the Barcelona Agreement and the discussions of the creation of a Mediterranean Union has awakened the interest of the non-EU Mediterranean countries to expand their exports to the European markets. This study analyses the factors that influence the German imports of olive oil by employing a gravity model. The results of two random-effects models corrected for serial correlation and heteroskedasticity suggest that being a Mediterranean Partner Country of the European Union has the highest impact on trade flows to Germany, thus supporting further Euromediterranean trade integration. Moreover, olive oil exports to Germany are positively related to the existence of direct marketing channels and to tourism. Therefore, these valuables should be explored more in the future by the Mediterranean countries so as to boost their exports. Key words: Euromediterranean trade integration; gravity model; olive oil; Germany
Keywords: 330